Gambaran Perkembangan Sosial Emosional pada Anak Usia Prasekolah - Anita Fitriyanti Simanjuntak Simanjuntak; Ganis Indriati; Rismadefi Woferst (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: One of the development aspects of preschool children is social-emotional development. Social-emotional development aims to make children have self-confidence, social skills, and the ability to control emotion. A mother has a very important role in providing stimulation related to development because a mother is a major caregiver for children. Therefore, this study aims to find out an overview of social-emotional development in preschool children. A research design used was descriptive quantitative. Methodology: The samples of the study were 99 respondents. The sampling technique used purposive sampling. The instrument for data collection used the PSC-17 questionnaire. The data analysis used was a univariate analysis. Results: Most of the children were 36-47 months, which were 43 respondents (43.4%), and the children were mostly male of 51 respondents (51.5%). There were no problems in social-emotional development in preschool children of 69 respondents (69.7%). Conclusion: It was obtained a conclusion that there were no problems found in social-emotional development in preschool children. For further researchers, factors influencing social-emotional development in preschool children can be studied.